Promoting mental health and community participation: A study on participatory arts practice, creativity and play in the city of Buenos Aires, Argentina - Bang, Claudia Lia (2015)
The purpose of this paper is to describe and analyze a participative health experience involving art, creativity and play, in articulation with the strategy of Comprehensive Primary Health Care focused on mental health. This experience is conducted by a network of institutions in Buenos Aires City. This is an exploratory and descriptive case study based on qualitative research methodologies. From an ethnographic perspective, the fieldwork revolved around interviews and participant observation records. The systematization process followed qualitative analysis content techniques. The outcomes describe a practice cored in intersectoral work, community participation, occupation of public space, creation of community gathering spaces and conformation of solidarity ties for addressing complex psychosocial issues. The main participatory processes focused on community organization and collective artistic creations are described. It is concluded that such experiences evidence substantial transformative potential, creating community conditions suitable for joint decision-making within the health-illness care process itself.